Bone and bone marrow involvement in neuroblastoma: A case report - Huang, Can (Medicine (Baltimore), 2020)
RATIONALE: Neuroblastoma (NB) can occur in any part of the sympathetic nervous system, and it is highly heterogeneous. Tumors that only involve bone marrow and bone lesions without solid masses have rarely been reported. PATIENT CONCERNS: A 2-year-old girl child presented with recurrent fever, accompanied by pain in both lower limbs for more than 1 month. DIAGNOSE: Bone marrow examination revealed NB cell invasion. Femoral and multiple vertebral lesions were observed by MRI, while head MRI, chest CT, abdominal CT, and pelvic CT showed no solid mass. INTERVENTIONS: The child received the standard therapy for high-risk NB. OUTCOMES: She was sensitive to the initial chemotherapy protocol. Two years later, a bone marrow examination confirmed NB recurrence. LESSONS: The prognosis of this special type of NB was not improved mainly based on common chemotherapy and local radiotherapy, and new treatment strategies should be explored.